Cooperative cognitive activity of students in the process of mathematical instruction; SGEM. 3rd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, vol. 3 - Gil L. B. Ludmila Boleslavna (2016, 2016)
Title screen